The problem of sense in violence. Contributions of the phenomenological-interpretative approach to the analysis of judicial sources (Palimpsesto, 2018)
The brief essay considers the problem of interpretation posed by “senseless violence”. For this aim, ittakes the phenomenological-interpretative approach developed by the Neue Gewaltsoziologie at the end ofthe nineteen-nineties in Germany and revisits its contributions and limits, by interpreting narratives ofviolence presented by two judicial sources. In this way, the article establishes the analytical potential ofthe somatic definition of violence and of the inquiry of its narrative articulation for the analysis of the useand meaning of violence.
Keywords: violence; Neue Gewaltsoziologie; phenomenology; meanings; judicial sources